Routes for Hydrogen Introduction in the Industrial Hard-to-Abate Sectors for Promoting Energy Transition - Alessandro Franco; Caterina Giovannini (Energies, 2023)
This paper offers a set of comprehensive guidelines aimed at facilitating the widespread adoption of hydrogen in the industrial hard-to-abate sectors. The authors begin by conducting a detailed analysis of these sectors, providing an overview of their unique characteristics and challenges. This paper delves into specific elements related to hydrogen technologies, shedding light on their potential applications, and discussing feasible implementation strategies. By exploring the strengths and limitations of each technology, this paper offers valuable insights into its suitability for specific applications. Finally, through a specific analysis focused on the steel sector, the authors provide in-depth information on the potential benefits and challenges associated with hydrogen adoption in this context. By emphasizing the steel sector as a focal point, the authors contribute to a more nuanced understanding of hydrogen’s role in decarbonizing industrial processes and inspire further exploration of its applications in other challenging sectors.